EFFECT OF USING WASTE PLASTIC AS A BINDING MATERIAL ON THE PERFORMANCE OF PLASTIC WASTE-BASED PAVING BLOCKS - Risman Firman; Joey Limbongan; Muhammad Ali Taufan (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
The increasing volume of plastic waste poses significant environmental challenges, particularly due to its slow degradation and the accumulation of non-biodegradable materials in landfills. This study explores an alternative utilization of plastic waste by transforming it into a binding material for paving blocks. A quantitative experimental approach was employed to examine how varying proportions of molten plastic and sand influence the physical and mechanical properties of paving blocks. Four mixture variations were tested 100% plastic, 75% plastic : 25% sand, 50% plastic : 50% sand, and 25% plastic : 75% sand, each molded into standard 20 × 10 × 8 cm specimens and evaluated for compressive strength, water absorption, and abrasion resistance. The results demonstrate a clear trend in which higher plastic content leads to improved mechanical performance. The 75% plastic composition exhibited the best overall results, achieving a compressive strength of 11.64 MPa, low water absorption of 1.32%, and an abrasion rate of 0.098 mm/min. The 100% plastic variation also performed well, with a compressive strength of 10.82 MPa and the lowest abrasion values ranging from 0.037 to 0.062 mm/min. In contrast, the low-plastic mixture (25%) showed a marked decline in performance, indicated by a compressive strength of 8.91 MPa, water absorption of 3.78%, and abrasion rates of 0.201–0.226 mm/min. Based on SNI 03-0691-1996, PB100 and PB75 meet Class A quality standards, PB50 is categorized as Class C, and PB25 falls into Class D. Overall, the findings confirm that plastic waste can serve as an effective binder, producing paving blocks with low porosity, high abrasion resistance, and enhanced mechanical properties. These results highlight the promising potential of plastic waste as a sustainable construction material, contributing to both waste reduction and the development of environmentally friendly building products.